Biomolecular Corona Associated with Nanostructures: The Potentially Disruptive Role of Raman Microscopy. Issue 11 (4th September 2021) - Battaglini, Matteo; Belenli Gümüş, Melike; Ciofani, Gianni
Abstract: When nanostructures and other materials are exposed to biological fluids, they are immediately covered by a layer of biological molecules, which is typically referred to as a "biomolecular corona" (BC). This represents the first component of a material that interacts with biological systems, so characterizing the composition and the dynamic evolution of BC is essential for predicting the interactions of materials and living organisms. This review provides an analysis of current BC characterization techniques, with particular attention to nanostructures involved in biomedical applications. The influence on cell–nanostructure interactions is assessed and the advantages and limitations of each technique are discussed and compared. An in‐depth analysis of Raman microscopy, a relatively unexploited tool with great potential in the characterization of BC, is then conducted. Raman microscopy can be used to analyze a vast amount of specimens without the need for staining, and can provide analysis on a spatial scale of hundreds of nanometers: it may thus represent a potentially disruptive tool for the characterization of BC, as it overcomes many of the limitations posed by current techniques. Abstract : Upon interaction with the biological environment, nanostructures are immediately covered by a biomolecular corona that determines the nanostructures' biological identity. This phenomenon can lead to potentially adverse effects or can also be exploited as a tool for new applications of the nanostructures. Raman microscopy can represent a potentially disruptive tool for revealing the composition of the biomolecular corona.